THE RELATIONSHIP BETWEEN THE AUDIT BOARD OF THE REPUBLIC OF INDONESIAâS (BPK) OPINION WITH REGIONAL GOVERNMENT FINANCIAL REPORT AND CORRUPTION - Idrus, Yudi Avalon; Achsani, Noer Azam; Hardiyanto, Arief Tri (Jurnal Tata Kelola & Akuntabilitas Keuangan Negara, 2018)
BPK audit report on a government financial report contains an opinion that is a professional statement of the auditor regarding the fairness of financial information presented in the financial statement. In forming opinion, a BPK auditor uses four criteria, namely the application of Government Accounting Standard, adequate disclosures, compliance of laws and regulations, and effectiveness of internal control systems. The unqualified opinion is issued to a financial report with no material statements and/or fraud.Â  However, it is widely reported that many irregularities still occur across government entities and cost the stateâs resources (finance). This study aims to analyze corruption committed by heads of local governments and its influence on BPK opinion build a model which shows the relationship between them. This study uses a model called ordinal logistic regression and found that there is a correlation between BPK opinion with corruption committed by heads of local governments. The best ordinal logistic regression model shows that BPK opinion is dominantly influenced by the compliance of government financial report with Government Accounting Standard, compliance with law and regulations and effectiveness of internal control systems.